A Bildung-psychological investigation into student motives: McKinsey- or von Humboldt-oriented?. Issue 6 (1st November 2016) - Koops, Willem; van den Kerkhof, Michael; Ostermeier, Carlien; van de Schoot, Rens
Abstract: This study examined differential student motives among students from a social sciences bachelor's degree, and whether this difference related to participating in educational programmes for broader intellectual formation (Bildung). Survey research was conducted among 432 Dutch students (79.5% female), ranging in age from 17 to 32 years ( M age  = 21.12, SD = 2.08). With five categories of questions, the survey assessed whether study motives corresponded to Bildung or vocational preparation. Results indicated an overall twocomponent structure, distinguishing Bildung motives (indicated as the von Humboldt component) from vocational preparation motives (indicated as the McKinsey component). In addition, respondents participating in a programme for broader intellectual formation or aspiring a research master's degree programme generally scored higher on Bildung and lower on vocational preparation compared to students who were not. Educational consequences of these findings are discussed. The main conclusion is that a von Humboldt perspective is feasible, since a substantial number of students share the von Humboldt perspective.